1999
DOI: 10.1093/jat/23.7.598
|View full text |Cite
|
Sign up to set email alerts
|

On-Line Immunoaffinity Extraction and HPLC Analysis of Flunitrazepam and Its Main Metabolites in Serum

Abstract: A sensitive, simple, and rapid method for the determination of flunitrazepam and its major metabolites (7-aminoflunitrazepam, 7-acetamidoflunitrazepam, and norflunitrazepam) in serum and plasma is presented. The on-line procedure uses an immobilized, highly reusable antibody against benzodiazepines for selective extraction from serum followed by analysis by high-performance liquid chromatography with ultraviolet detection. This reliable method provides a limit of detection of 1 ng/mL serum, and results are obt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…On-line immunoaffinity chromatography coupled with RP chromatography and a radioimmunoassay was developed for analyzing 4-[(5,6,7,8-tetrahydro-5,5,8,8-tetramethyl-2-naphthyl)-carbamoyl] benzoic acid in human plasma [222]. Another study reported an on-line immunoextraction method for the determination of flunitrazepam and its major metabolites in serum and plasma [223].…”
Section: Biointeraction Studiesmentioning
confidence: 99%
“…On-line immunoaffinity chromatography coupled with RP chromatography and a radioimmunoassay was developed for analyzing 4-[(5,6,7,8-tetrahydro-5,5,8,8-tetramethyl-2-naphthyl)-carbamoyl] benzoic acid in human plasma [222]. Another study reported an on-line immunoextraction method for the determination of flunitrazepam and its major metabolites in serum and plasma [223].…”
Section: Biointeraction Studiesmentioning
confidence: 99%
“…Senstivities of the methods are typically not better than 1 ng/mL. To address these issues, a column-switching method employing an anti-benzodiazepine immunoaffinity column for on-line sample pre-treatment has been reported [21]. By this method sample pre-treatment and analysis was automated, total analysis time was under 40 min and the reported limit of detection was 1 ng/mL.…”
Section: Requirements For Flunitrazepam Analysismentioning
confidence: 99%
“…This technique has already been successfully applied for on-line or separate purification and extraction in several cases [22][23][24], e.g. for the extraction of estradiol [25], clenbuterol [26], amanitin [27], tetrahydrocannabinol [28,29], benzodiazepines and their metabolites [30,31], LSD [32,33] and morphine and its metabolites [34,35]. We developed a new immunoadsorber for the extraction of morphine and its glucuronides by the immobilisation of specific antibodies against morphine and morphine glucuronides [36] applying the solgel method.…”
Section: Introductionmentioning
confidence: 99%